2020
DOI: 10.1002/pssa.202000223
|View full text |Cite
|
Sign up to set email alerts
|

Study of SiO2 Etching Processing with CH4/SF6 Plasmas

Abstract: Silicon dioxide (SiO2) layers using photoresist (PR) masks are etched by inductively coupled plasma in CH4/SF6 under various etching conditions. A thin CHxFy polymer layer which exists on the surface of sample during steady‐state etching is observed. The steady‐state CHxFy layer reduces the physical sputtering of ions, resulting in the etching rate of PR decreases significantly. Although the high‐density plasmas can enhance the physical sputtering to some extent and give SiO2 more opportunities to react with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The sputtering of groups from the CH x F top layer generates defect points where the reaction of neutral F can promptly erode the whole structure beneath, creating pores in the initially uniform layer. Thus, the observed pores in the treated SB investigated here (micrographs) are attributed to the simultaneous physical (sputtering) and chemical (etching) effect of the SF 6 plasmas as demonstrated in the work (Man et al 2020).…”
Section: Characterization Of the Adsorbentsmentioning
confidence: 51%
See 1 more Smart Citation
“…The sputtering of groups from the CH x F top layer generates defect points where the reaction of neutral F can promptly erode the whole structure beneath, creating pores in the initially uniform layer. Thus, the observed pores in the treated SB investigated here (micrographs) are attributed to the simultaneous physical (sputtering) and chemical (etching) effect of the SF 6 plasmas as demonstrated in the work (Man et al 2020).…”
Section: Characterization Of the Adsorbentsmentioning
confidence: 51%
“…Moreover, ion bombardment favors the non-homogeneous removal of material. In the work of Man (Man et al 2020), it was demonstrated that etching of SiO 2 coated with an CH x F layer, in SF 6 /CH 4 plasmas, is regulated, amongst others, by ion bombardment. The sputtering of groups from the CH x F top layer generates defect points where the reaction of neutral F can promptly erode the whole structure beneath, creating pores in the initially uniform layer.…”
Section: Characterization Of the Adsorbentsmentioning
confidence: 99%
“…We believe that this tendency can be attributed to the formation of a steady-state layer on the surface after long-time etching. 43 The average area of a single rod was calculated from SEM images using ImageJ as shown in Fig. 2c.…”
Section: Physical Characterization Of the Modified Fep Filmmentioning
confidence: 99%